2015
DOI: 10.1002/esp.3745
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem carbon stocks across a tropical intertidal habitat mosaic of mangrove forest, seagrass meadow, mudflat and sandbar

Abstract: Intertidal habitats provide numerous ecosystem services, including the sequestration and storage of carbon, a topic of great recent interest owing to land-cover transitions and climate change. Mangrove forests and seagrass meadows form a continuum of intertidal habitats, alongside unvegetated mudflats and sandbars, however, studies that consider carbon stocks across these spatially-linked, threatened ecosystems are limited world-wide. This paper presents the results of a field-based carbon stock assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 60 publications
6
38
5
Order By: Relevance
“…The smaller species, H. ovalis, showed almost constant pattern of carbon content in the top and medium layers, with a small increase in the bottom layer of sediment (Figure 4). Our results reported much lower organic carbon (%) than the study of Prathep (2012) and higher values than the study by Rattanachot and Prathep (2015) in Thailand and lower values reported in Singapore by Phang et al (2015). The results from the organic carbon in the sediment suggested that bigger species such as E. acoroides store more carbon than the smaller and medium size species.…”
Section: Organic Carbon In the Sedimentcontrasting
confidence: 70%
See 1 more Smart Citation
“…The smaller species, H. ovalis, showed almost constant pattern of carbon content in the top and medium layers, with a small increase in the bottom layer of sediment (Figure 4). Our results reported much lower organic carbon (%) than the study of Prathep (2012) and higher values than the study by Rattanachot and Prathep (2015) in Thailand and lower values reported in Singapore by Phang et al (2015). The results from the organic carbon in the sediment suggested that bigger species such as E. acoroides store more carbon than the smaller and medium size species.…”
Section: Organic Carbon In the Sedimentcontrasting
confidence: 70%
“…The average worldwide organic carbon content of the living seagrass biomass is 2.52±0.48 Mg C ha -1 (Fourqurean et al 2012b), wherein the results of our study suggest 3.2 and 1.3-fold increase for bigger seagrass and medium size species, 4.5-fold decrease for small size species. In Southeast Asian region, our study suggested much higher carbon content in the above and below ground parts than reported by Phang et al (2015) and Prathep (2012), while Supriadi et al (2014) reported much higher values. The variations of the carbon pool are based on the species size, as the bigger species have longer-lived vegetation parts and lower leaf production rates.…”
Section: Results and Discussion Biomass And Carbon Storage In The LIVcontrasting
confidence: 49%
“…Across the western quarter of the Southeast region, the lagoon’s seagrass total stock densities to 1 m of sediment are in general agreement to one another. For seagrasses of Chek Jawa, Singapore, within the shelter and embayment of the Johor straights, the carbon stocks were measured at around 138 ± se 8.6 Mg C ha -1 of (Phang, Chou and Friess, 2015). The island estuaries/lagoons of the Indonesian Archipelago to the immediate south of Borneo were measured at around the 129.9 ± se 9.6 Mg C ha -1 , and 24 Mg C ha -1 within the more open turbulent coastal systems of its Pacific side (Alongi et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…C standing stocks and fluxes can be substantial but are highly variable even among a single wetland type (Breithaupt et al, 2012;Chmura et al, 2003;Mcleod et al, 2011), as local variation in rainfall regime, mean annual temperature minima, vegetation structure, and geomorphology, for example, are important determinants for how C is budgeted (Yando et al, 2016). Multiple relevant C assessments have been conducted in coastal wetlands (e.g., Adame et al, 2013;Bhomia et al, 2016;Donato et al, 2011Donato et al, , 2012Duarte et al, 2010;Fourqurean et al, 2012;Jones et al, 2014;Kauffman et al, 2011;Livesley & Andrusiak, 2012;Lovelock et al, 2015;Marchand, 2017;Marchio et al, 2016;Murdiyarso et al, 2015;Nam et al, 2016;Phang et al, 2015;Smoak et al, 2013;Stringer et al, 2015). Yet C storage and associated transformations can occur in wetlands much farther inland along tidal rivers than are currently assessed, including tidal freshwater (salinity ≤0.5 psu) and oligohaline (salinity 0.5-5.0 psu) wetlands within the upper estuary.…”
Section: Introductionmentioning
confidence: 99%